Review of activity in CSA standards activity in industrial noise - Kelsall, Tim (Canadian Acoustics, 2002)
This paper reviews recent activities in the Canadian Standards Association Industrial Noise Subcommittee, the most active acoustics standards group in Canada. Recent activities have included a new voluntary standard on Noise Emission Declarations, an acoustics section in the recent Office Ergonomics standard and ongoing work in adapting ISO standards on community noise measurement to Canada. In addition, there is a joint working group with ANSI looking at a North American approach to the ISO industrial noise propagation standard. Future opportunities, such as in-plant noise predictions, will be discussed. Recent publications and ongoing activity will be summarised and opportunities for wider involvement of the acoustics community across Canada encouraged.